2020
DOI: 10.1088/2053-1591/ab949f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the atmosphere and Mn doping on the electrical properties of Sr2Fe1−xMnxNbO6 and their mechanisms

Abstract: Double-perovskite composite oxides (A 2 BB′O 6 ) usually have excellent functional properties and are widely studied and applied. Its electrical, magnetic or other properties can be optimized by doping transition metal elements at its B or B′ site. In this paper, the effects of Mn doping and testing atmosphere on the crystal structures and the electrical conductivities of Sr 2 Fe 1−x Mn x NbO 6 (SFMN) were systematically investigated. The experimental results demonstrate that the conductivities of SFMN will in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 39 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…The authors concluded that through doping Mn in the B-site of the SFN double perovskite the conductivity increases in air but decreases under reducing atmospheres. 401 The observed increase in conductivity in air through doping the B-site of SFN was confirmed by other authors as well. 398 They achieved a maximum conductivity of 5.7 S cm −1 at 800 °C for a Co-doped Sr 2 Fe 0.1 Co 0.9 NbO 6 .…”
Section: Solid Oxid Electrolysis Cell Componentssupporting
confidence: 76%
See 4 more Smart Citations
“…The authors concluded that through doping Mn in the B-site of the SFN double perovskite the conductivity increases in air but decreases under reducing atmospheres. 401 The observed increase in conductivity in air through doping the B-site of SFN was confirmed by other authors as well. 398 They achieved a maximum conductivity of 5.7 S cm −1 at 800 °C for a Co-doped Sr 2 Fe 0.1 Co 0.9 NbO 6 .…”
Section: Solid Oxid Electrolysis Cell Componentssupporting
confidence: 76%
“…The chemical stability of Mn-doped SFN double perovskites after heat treatment in a reducing atmosphere (80% H 2 O + 20% H 2 /air, 900 °C, 24 h) was analyzed by XRD measurements. 401 The oxidized and reduced Mn-SFN powders showed no apparent differences in the XRD patterns for a low doping content of 0 ≤ x ≤ 0.2. Nevertheless, a shift from high-angle peaks to smaller angles was observed with increasing Mn content.…”
Section: Solid Oxid Electrolysis Cell Componentsmentioning
confidence: 90%
See 3 more Smart Citations